Santiago de Cali y el Palacio Nacional de Justicia - Hincapié Aristizábal, Ricardo (Colección Libros de investigación (Cali, Colombia), 2018)
This study includes two parts dealing respectively the urban context of the National Palace, understood as the Plaza de Cayzedo or as the traditional center of the city and the architecture itself. The first part seeks to explain the historical evolution of the square and the site where the National Palace was built. In the second part the focus is synchronous, the time frame is the twentieth century, and the years 1926-1933 during the construction period of the National Palace.